Effect of different zinc concentrations on partially-stabilized cement for vital pulp therapy - Chih-Chun Chang; Chun-Liang Yeh; Hao-Hueng Chang; Yi-Fang Kuo; Po-Ya Huang; Chun-Pin Lin (Journal of the Formosan Medical Association, 2019)
Background/Purpose: We have developed and investigated the partially-stabilized cements (PSC) with Zn for vital pulp therapy due to their short setting time and high cell biocompatibility. However, the effect of PSC with different concentrations of Zn on setting time and biocompatibility remained unknown. Therefore, the purpose of this study was to determine the optimal concentration of Zn to be synthesized with PSC for vital pulp therapy. Methods: PSC with different weight percentages of Zn (5%, 7%, 10%) were synthesized to attain 5%Zn-PSC, 7%Zn-PSC, and 10%Zn-PSC. The initial and final setting times were measured using the Gillmore needles method, and the compressive strength tests were conducted using a universal testing machine. The phases of Zn-PSC powders were observed using an X-ray diffractometer (XRD). Human dental pulp stem cells (hDPSCs) were used to evaluate the biocompatibility and cytotoxicity of the materials via Alamar blue and LDH assays. Mineral trioxide aggregate (MTA) was used to be compared with Zn-PSC samples. Results: The initial and final setting times of PSC with different concentrations of Zn were reduced considerably compared to those of MTA. The results also indicated that the initial and final setting times decreased as the weight % of Zn increased. 5%Zn-PSC had the highest compressive strength among all tested materials. 5%Zn-PSC samples also displayed comparatively higher cell biocompatibility than 7% and 10% Zn-PSC samples. However, there was no significant difference between the 5%Zn-PSC and MTA in cell biocompatibility. In addition, the results of the LDH release assay indicated a low level of cytotoxicity among all the test samples. Conclusion: 5%Zn-PSC has a shorter setting time, better mechanical properties, and good biocompatibility and thus it has great potential for vital pulp therapy. Keywords: Vital pulp therapy, Partially-stabilized cement, Zinc, Setting time, Biocompatibility